Lipoprotein(a) in patients with aortic stenosis: Insights from cardiovascular magnetic resonance. - Vassilios S Vassiliou; Paul D Flynn; Claire E Raphael; Simon Newsome; Tina Khan; Aamir Ali; Brian Halliday; Annina Studer Bruengger; Tamir Malley; Pranev Sharma; Subothini Selvendran; Nikhil Aggarwal; et al. (PLoS ONE)
Background Aortic stenosis is the most common age-related valvular pathology. Patients with aortic stenosis and myocardial fibrosis have worse outcome but the underlying mechanism is unclear. Lipoprotein(a) is associated with adverse cardiovascular risk and is elevated in patients with aortic stenosis. Although mechanistic pathways could link Lipoprotein(a) with myocardial fibrosis, whether the two are related has not been previously explored. In this study, we investigated whether elevated Lipoprotein(a) was associated with the presence of myocardial replacement fibrosis. Methods A total of 110 patients with mild, moderate and severe aortic stenosis were assessed by late gadolinium enhancement (LGE) cardiovascular magnetic resonance to identify fibrosis. Mann Whitney U tests were used to assess for evidence of an association between Lp(a) and the presence or absence of myocardial fibrosis and aortic stenosis severity and compared to controls. Univariable and multivariable linear regression analysis were undertaken to identify possible predictors of Lp(a). Results Thirty-six patients (32.7%) had no LGE enhancement, 38 (34.6%) had midwall enhancement suggestive of midwall fibrosis and 36 (32.7%) patients had subendocardial myocardial fibrosis, typical of infarction. The aortic stenosis patients had higher Lp(a) values than controls, however, there was no significant difference between the Lp(a) level in mild, moderate or severe aortic stenosis. No association was observed between midwall or infarction pattern fibrosis and Lipoprotein(a), in the mild/moderate stenosis (p = 0.91) or severe stenosis patients (p = 0.42). Conclusion There is no evidence to suggest that higher Lipoprotein(a) leads to increased myocardial midwall or infarction pattern fibrosis in patients with aortic stenosis.